Secondary plasma formation after single pulse laser ablation underwater and its advantages for laser induced breakdown spectroscopy (LIBS). Issue 21 (16th May 2016) - Gavrilović, M. R.; Cvejić, M.; Lazic, V.; Jovićević, S.
Abstract : We demonstrated that well resolved and intense spectral lines can be obtained by single pulse laser excitation underwater if recording only secondary plasma emission using large acquisition gate widths. Abstract : In this work we present studies of spatial and temporal plasma evolution after single pulse ablation of an aluminium target in water. The laser ablation was performed using 20 ns long pulses emitted at 1064 nm. The plasma characterization was performed by fast photography, the Schlieren technique, shadowgraphy and optical emission spectroscopy. The experimental results indicate the existence of two distinct plasma stages: the first stage has a duration of approximately 500 ns from the laser pulse, and is followed by a new plasma growth starting from the crater center. The secondary plasma slowly evolves inside the growing vapor bubble, and its optical emission lasts over several tens of microseconds. Later, the hot glowing particles, trapped inside the vapor cavity, were detected during the whole cycle of the bubble, where the first collapse occurs after 475 μs from the laser pulse. Differences in the plasma properties during the two evolution phases are discussed, with an accent on the optical emission since its detection is of primary importance for LIBS. Here we demonstrate that the LIBS signal quality in single pulse excitation underwater can be greatly enhanced by detecting only the secondary plasma emission, and also by applying long acquisition gates (in the order of 10–100 μs). The presented results are of great importance for LIBS measurements inside a liquid environment, since they prove that a good analytical signal can be obtained by using nanosecond pulses from a single commercial laser source and by employing cost effective, not gated detectors.